Survey of Difficult Experiences of Nurses Caring for Patients Undergoing Radiation Therapy: An Analysis of Factors in Difficult Cases - Tsuchihashi, Yumiko; Matsunari, Yuko; Kanamaru, Yumiko (Asia-Pacific journal of oncology nursing, 2018)
The purpose of this study was to analyze the difficult experiences of nurses who cared for patients undergoing radiation therapy and factors related to patient feelings toward the progress and difficulties of treatment and the kind of care needed. A descriptive survey using a questionnaire. Anonymous self-report data were collected from a sample of 228 nurses who had 2-5 years of nursing experience in a National University Hospital in Japan. Years of working experience; knowledge and training in radiation therapy and difficult experiences of nurses caring for patients undergoing radiation therapy. In hospital "A", about 80% of the nurses had cared for patients undergoing radiation therapy, and about 40% had experience with difficult cases. The characteristics of competent nurses in radiation nursing were the following: while not having knowledge and experience, they were seriously facing their patients. However, the treatment process could not be predicted, skills related to the whole-human involvement of patients were insufficient, and communication was similar. In addition, the characteristics of competent nurses in radiation nursing became apparent. Although these nurses lacked knowledge and experience, they interacted with patients in a serious manner. However, the treatment process could not be predicted, and the skills related to the holistic involvement of patients were insufficient. Furthermore, communication between the nurses and patients was difficult. Competent nurses with 2-5 years of working experience, but lacking specific knowledge and experience regarding radiation therapy could cope with difficult radiation therapy cases. However, additional education, training, and mentoring from expert nurses would improve the quality of care for patients undergoing radiation therapy and reduce distress for nurses with less experience. In this study, the need for educational measures and a support system to help competent nurses face difficult cases were suggested.